Poly(lactic acid) composites with few layer graphene produced by noncovalent chemistry. Issue 11 (7th September 2022) - Peixoto, Tânia; Nunes, Joana; Lopes, Maria A.; Marinho, Elina; Proença, M. Fernanda; Lopes, Paulo E.; Paiva, Maria C.
Abstract: In recent years, significant attention has been given to "green" product innovation and related manufacturing processes. This work reports the preparation of few‐layer graphene (FLG) and respective PLA‐based composites by an eco‐friendly, efficient, and cost‐effective approach. FLG was produced in a scaled‐up process, based on the noncovalent functionalization of a micronized graphite with a pyrene derivate (PY), in aqueous solution. The exfoliation degree, morphology, and thermal stability of the exfoliated material were evaluated. Then, the influence of the pristine graphite and FLG on the morphology, crystallinity, thermal and mechanical properties of PLA composites produced by melt mixing is reported for the first time. The composites prepared with the lowest loading of 0.05 wt% demonstrated suitability for further processing for potential applications where product safety is crucial, such as in biomedicine. Abstract :